The Implementation Of Ecology-Based Islamic Education Model In Baitul Ulum Islamic Boarding School At Mojoduwur-Mojowarno Jombang - Imam Ghozali (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Education is an effort to optimize human potential in its entirety, potential, humanity and natural potential (environment) that as an effort to ask Islamic students to the realization of righteous human beings. Baitul Ulum Mojoduwur Jombang Islamic Boarding School guides students to carry out activities to maintain the cleanliness of the Islamic boarding school environment (natural potential) as a form of implementation of an ecological based Islamic education model. Therefore, the purpose of this study is to describe the forms of activities to maintain the cleanliness of the environment of Islamic boarding schools in the ecology-based Islamic education model and the ecological concept in the fiqh perspective and the problematic implementation of ecology-based Islamic education in Baitul Ulum Islamic Boarding School. Descriptive analysis types qualitative research, with data collection techniques namely observation, interviews and documentation. Data analysis techniques are the description, reduction and interpretation. The results of the discussion that the concept of ecological-based Islamic education in its application can be reflected in two models. First, the classical model, which is applicative, still uses the Islamic distinctive cultures, such as Roanan (workmanship) once a week, and cleaning pickets clean the cottage environment. Second, the modern model, namely by utilizing natural technological advances such as findings in the field, is to replant the land around the hut and fertilizing it with natural fertilizers. The problem of the implementation of Ecological-based Islamic education in Baitul Ulum Mojoduwur Mojowarno Jombang Islamic Boarding School is the existence of historical factors, land factors, and the density of literary activities with the activities of reciting and attending school making the implementation of ecologically based Islamic education models only a small part in its application.